Virginity as an Ethical Value in the Qur’an: An Analysis of Al-Azhar’s Tafsir on QS. Al-Waqi’ah Verse 36 - Ahmad Naufal Afifi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This article attempts to explore the concept of virginity in Buya Hamka’s Tafsir Al-Azhar through a Qur’anic ethical approach oriented towards the values of purity (thaharah) and self-control (iffah). This study is motivated by the complexity of the issue of virginity in contemporary Islamic ethical discourse, which is not only biological in nature, but also theological, moral, and social. This study aims to reveal how Hamka interprets the term abkār in QS. Al-Waqi’ah verse 36 as a spiritual symbol of purity of the soul, not merely physical pleasure. Using a qualitative research method based on library research and a thematic interpretation approach (tafsīr mauḍū’ī), this study explores religious texts and supporting literature through linguistic, theological, and contextual ethical analysis. The analysis was conducted descriptively and analytically with triangulation of sources to maintain data validity. The results of the study show that Hamka shifts the meaning of virginity from the biological realm to the universal spiritual and moral realm, so that purity is understood as an ethical process that demands equal moral responsibility for men and women. This concept makes an important contribution to the renewal of Islamic ethics that is gender-equitable and relevant to the moral dynamics of modern society. The results of the study show that virginity in Hamka’s perspective is a symbol of spiritual purity that represents the perfection of faith and moral integrity of believers.